THE INFLUENCE OF THE PROBLEM-BASED LEARNING MODELS ON GLOBAL WARMING MATERIALS AGAINST STUDENTS LEARNING RESULTS AT SMA NEGERI 1 BENGKUNAT - Beria Arada; Abdurrahman Abdurrahman; Doni Andra; I Wayan Distrik (Universitas Sriwijaya, 2022)
A problem found in the learning process is that the learning model used is unappropriated so that the students are less active and don't master the subject matter instruction. This study aims to determine the effect of problem-based learning model on global warming material on student learning outcomes. This research was conducted at SMA Negeri 1 Bengkunat with a sample of 28 people. The data collection techniques used is the pretest and posttest questions, which were previously tested for validity and reliability. The data analysis techniques use the-count test paired test, namely sig. 0.364 is greater than 0.05. The results showed that there was an effect of the problem-based learning models on global warming material on learning outcomes. Keywords: learning outcomes, problem-based learning.